Septuagint Exodus 12-23 and Mekilta : examples of early Jewish exegesis? - Buchner, Dirk Leonardus (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Litt.) -- University of Stellenbosch, 1994.